Successful Surgical Management of Giant Condyloma Acuminatum (Buschke Lowenstein Tumor) in the Urethra of a Female Patient: A Case Report - Nordsiek, Michael (Curr Urol, 2015)
The Buschke-Lowenstein tumor (BLT) is a slow-growing, locally destructive verrucous plaque that typically appears on the penis but may occur elsewhere in the anogenital region. It most commonly is considered to be a regional variant of verrucous carcinoma. It is rare but accounts for 5-24% of all penile cancers. It can also affect the perineum and other portions of the genitalia. It was first described by Buschke and Löwenstein in 1925, and is also known as giant condyloma acuminatum (GCA). Regardless of the treatment modality, careful follow-up is recommended because of the high risk of recurrence and the possibility for malignant transformation in 30-56% of patients. We present a case of a 47-year-old Hispanic female that presented to the urology clinic for dysuria and upon work-up was found to have a GCA. GCA typically affects the penis, although the perianal region, vulva, vagina, rectum, scrotum, perineum and bladder may be involved. To date, we believe this is the only reported case of GCA in the urethra of a female patient with sparing of the bladder. This lesion was successfully removed with wide local excision. We believe that further studies are needed to define this disease, identify its pathogenesis, and the most successful treatment protocol.